Unwilling Avatars: Idealism and Discrimination in Cyberspace - Franks, Mary Anne (Columbia Journal of Gender and Law, 2011)
Few would deny that cyberspace has a dark side. The of such negative incidents and perhaps even more widely as to the appropriate response to these incidents. On one side are voices calling for increased regulation of the Internet: user codes of conduct, the reform of Section 230 of the 1996 Communications Decency Act (CDA § 230), and stricter laws regarding online defamation, threats, and invasions of privacy. On the other side are those who argue that the benefits offered by the free and unregulated exchange of ideas that characterizes the medium of cyberspace far outweigh the harms facilitated by the Internet. The latter view is based on what this Article calls cyberspace idealism- the view of cyberspace as a utopian realm of the mind where all can participate equally, free from social, historical, and physical restraints. Though the high-flown rhetoric of early cyberspace idealists may now seem somewhat dated, the liberationist vision at its core maintains its hold on our (increasingly online) collective imagination. This vision is a quasi-Cartesian one: a vision of human identity as fundamentally divided between mind and matter, where matter is limiting and temporal and, as such, in many ways inferior to the mind. For those who hold this vision, cyberspace presents the opportunity to escape physical limitations, both geographic and bodily.